Sanksi Pidana Terhadap Pelaku Importir Pakaian Bekas - Oqsana Lubis, Haviza; Abduh, Rachmad (Universitas Ekasakti, 2024)
Clothing is an essential need that is as important as food and shelter for humans. For business actors, this creates new business opportunities to provide quality clothing with various types and models but at affordable prices, so the idea arises for business actors to import used clothing. Importing used clothes is the activity of bringing used clothes from abroad into the country. These used clothes are offered at more affordable prices. This research aims to determine criminal sanctions against perpetrators who import used clothing. The method used in this research is normative juridical. The data analysis method is carried out by collecting data by reviewing primary legal materials and library materials or secondary legal materials, both in the form of documents and applicable laws and regulations. In Law Number 7 of 2014 concerning trade, regulations and sanctions are regulated against importers of used goods. The results of this research indicate that the import and trade of used clothing in Indonesia is an economic crime and is punishable by criminal penalties. Importing second-hand clothing is a criminal act of commissionism, namely a criminal act resulting from a violation of the orders of Law Number 7 of 2014 concerning Trade. Each violation carries a maximum prison sentence of 5 years with a maximum fine of 5 billion rupiah.